2003
DOI: 10.1542/peds.111.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Does Stimulant Therapy of Attention-Deficit/Hyperactivity Disorder Beget Later Substance Abuse? A Meta-analytic Review of the Literature

Abstract: Objective.Concerns exist that stimulant therapy of youths with attention-deficit/hyperactivity disorder (ADHD) may result in an increased risk for subsequent substance use disorders (SUD). We investigated all long-term studies in which pharmacologically treated and untreated youths with ADHD were examined for later SUD outcomes. Methods.A search of all available prospective and retrospective studies of children, adolescents, and adults with ADHD that had information relating childhood exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
355
3
26

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 752 publications
(405 citation statements)
references
References 46 publications
17
355
3
26
Order By: Relevance
“…In humans, the use of psychostimulant treatment for ADHD may protect against the development of substance use disorders [12,49,52,91], especially if treatment is started in childhood [for a review, see 43]. Conversely, the present results may also suggest that use of psychostimulants by individuals without ADHD could increase the risk of substance abuse problems.…”
Section: Discussionmentioning
confidence: 85%
“…In humans, the use of psychostimulant treatment for ADHD may protect against the development of substance use disorders [12,49,52,91], especially if treatment is started in childhood [for a review, see 43]. Conversely, the present results may also suggest that use of psychostimulants by individuals without ADHD could increase the risk of substance abuse problems.…”
Section: Discussionmentioning
confidence: 85%
“…The available clinical data suggest that, whether or not sensitisation occurs, the net effect of treating children and young people with AD/HD with stimulant medication is to protect against, rather than lead to, later substance misuse. A meta-analysis of the available literature reported that those treated with stimulants were protected against the development of substance misuse problems by a factor of almost two (Odds Ratio, 1.9), compared with those whose AD/HD was not treated with stimulant medication [184]. Possible mechanisms for this protective effect include a reduction in AD/HD symptoms especially impulsive behaviour, a reduction in conduct disorder and later anti-social personality disorder, im-proved academic performance and career, or improved peer and family relationships.…”
Section: ■ Abuse Potential Of Psychostimulantsmentioning
confidence: 99%
“…This was consistent with an earlier meta-analysis. 83 However, a 36-month follow-up of the MTA study 84 and a 10-year follow-up study of a clinical sample 85 found no association between ADHD treatment and rates of substance use. Additional studies assessing large samples and following up participants into adolescence and/or adulthood are necessary to determine whether treatment has a protective effect on substance use rates and development of dependence.…”
Section: Functional Outcomesmentioning
confidence: 97%